2010
DOI: 10.1186/1824-7288-36-26
|View full text |Cite
|
Sign up to set email alerts
|

Role of adiponectin and leptin on body development in infants during the first year of life

Abstract: BackgroundThe control of growth and nutritional status in the foetus and neonate is a complex mechanism, in which also hormones produced by adipose tissue, such as adiponectin and leptin are involved. The aim of this study was to evaluate levels of adiponectin, leptin and insulin in appropriate (AGA) and small for gestational age (SGA) children during the 1st year of life and to correlate these with auxological parameters.MethodsIn 33 AGA and 29 SGA infants, weight, length, head circumference, glucose, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
3
27
0
7
Order By: Relevance
“…Insulin levels increase until 1 year of age, which is accompanied by a reduction in adiponectin; however, those changes are not associated with HOMA [79]. The inverse association between total and HMW adiponectin with IR seems to appear only after 2-6 years of age [11,14,26,80,81].…”
Section: Insulin Resistancementioning
confidence: 98%
“…Insulin levels increase until 1 year of age, which is accompanied by a reduction in adiponectin; however, those changes are not associated with HOMA [79]. The inverse association between total and HMW adiponectin with IR seems to appear only after 2-6 years of age [11,14,26,80,81].…”
Section: Insulin Resistancementioning
confidence: 98%
“…However, as weight gain progressed, leptin concentrations increased significantly (5,19,31). It has been speculated that these increased leptin levels may derive from the increase in adipose fat typically observed after the under-nutrition period in preterm infants, suggesting a possible involvement of leptin in the early development of insulin resistance (32,33). A series of epidemiological human and experimental animal studies have shown that exposure to inadequate (high or low) nutrition during fetal and postnatal life, as well as reduced fetal growth followed by excessive postnatal catch-up in height and particularly, in weight, increase the risk of obesity, insulin resistance and type 2 diabetes in childhood and adult life (34).…”
Section: Pregnancy and Intrauterine And Neonatal Developmentmentioning
confidence: 98%
“…Bozzola et al (32) evaluated both total and isoform adiponectin circulating levels in a cohort of infants, and found a significant increase from birth up to the first month of life, followed by a decline at one year of age in all subjects. The investigators argued that the observed fall in serum adiponectin levels may be a consequence of increased adiposity, confirming the negative association between serum adiponectin levels and percentage of body fat, as is the case in older children (32).…”
Section: Pregnancy and Intrauterine And Neonatal Developmentmentioning
confidence: 99%
“…Bozzola et al, 48 avaliaram os níveis de leptina e adiponectina nos grupos de crianças com peso ao nascimento < -2 desvios-padrão e > -2 desvios-padrão para a idade gestacional e observaram que, para ambos os grupos, o nível de adiponectina aumentou no primeiro mês mas, com o aumento da idade, houve uma diminuição progressiva deste hormônio, enquanto que a leptina se manteve maior durante todo o primeiro ano de vida naqueles com maior peso ao nascer. O padrão de isoforma de adiponectina é alterado em crianças pequenas para idade gestacional o que Ibáñez et al, 49 supõem ser uma estratégia adaptativa de sobrevivência preparando-os para a aceleração compensatória do crescimento pós-natal.…”
Section: Tecido Adiposo Leptina E Adiponectinaunclassified
“…Isto possivelmente se deve aos diferentes métodos utilizados para classificar o crescimento fetal através do peso ao nascimento e ao número reduzido de estudos que controlam os fatores de confundimento. As classificações de baixo peso ao nascer (peso menor que 2500 g) para os que nascem entre 37 e 42 semanas de gestação 12 e pequeno para a idade gestacional (peso menor que percentil 10) 18 ou (< -2 desvio-padrão) 48 são inferidas nos estudos como uma proxy da restrição do crescimento intrauterino.…”
Section: Peso Ao Nascer E Medidas Corporaisunclassified